Implementation of character education in matshematics learning in elementary school - Aristanto Aristanto; Nanda Dwi Rohmah (Institute of Computer Science (IOCS), 2023)
The implementation of character education in elementary schools needs to be carried out on all sides on an ongoing basis. To develop character education in mathematics learning, it can be done by developing the content of mathematics lessons, selecting approaches, methods, or learning strategies to be used, as well as the mathematics learning process. This research is a qualitative research that uses a normative descriptive approach. Data collected by conducting interviews, observation and documentation. The results show that the implementation of education in mathematics can be realized based on the targets to be achieved by the researchers. Character education that is built through this learning is the values ??taught based on subjects such as discipline, independence, cooperation, and responsibility. In addition, learning activities that activate students through projects or problem solving will provide space for students to develop character values ??in learning mathematics. Integration is done by combining the character values ??in the lesson plans and students' consistency in applying these values ??outside of school. In measuring results, the teacher gives an assessment book to students.